The effect of inclusive leadership on innovative work behavior mediated by perceived organizational support - Hadisuwito, Mutiara Septiani; Yokanan, Raden Teja; Kaloeti, Ade Kristianus (PHINISI, 2025)
This study investigates the impact of inclusive leadership on innovative work behavior, emphasizing the mediating role of perceived organizational support. Using a quantitative approach, data were collected from 102 employees of through questionnaires distributed using a saturated sampling technique. Data were analyzed with version 4.1, employing validity and reliability tests (convergent validity, discriminant validity, average variance extracted, composite reliability, and Cronbach’s Alpha) as well as structural model assessments (R-square, goodness of fit, and P-Value). The results show that inclusive leadership positively influences both perceived organizational support and innovative work behavior, and that perceived organizational support also positively affects innovative work behavior. Furthermore, perceived organizational support mediates the relationship between inclusive leadership and innovative work behavior. However, the study is limited by its small sample size, focus on a single organization, reliance on self-reported data, and cross-sectional design, which constrain the generalizability and causal interpretation of the findings. Despite these limitations, the study suggests that fostering inclusive leadership and enhancing perceived organizational support can promote innovative work behavior. These findings offer valuable insights for human resource and leadership development strategies aiming to build more innovative and supportive workplace cultures.